A family with interleukin-17 receptor A deficiency: a case report and review of the literature - Kilic, Mehmet; Ozcan, Mehmet Hazar; Taskin, Erdal; Sen, Askin (Turkish J Pediatrics, 2023)
Background. Chronic mucocutaneous candidiasis (CMC) is characterized by recurrent or persistent infections of the skin, nail, oral, and genital mucosa with Candida species, mainly Candida albicans. In a single patient, the first genetic etiology of isolated CMC autosomal recessive interleukin-17 receptor A (IL-17RA) deficiency was reported in 2011.Case. We report four patients with CMC who displayed autosomal recessive IL-17RA deficiency. The patients were from the same family, and their ages were 11, 13, 36, and 37 years. They all had their first CMC episode by six months of age. All patients manifested staphylococcal skin disease. We documented high IgG levels in the patients. In addition, we found the coexistence of hiatal hernia, hyperthyroidism, and asthma in our patients.Conclusions. Recent studies have provided new information on the heredity, clinical course, and prognosis of IL-17RA deficiency. However, further studies are needed to reveal the full picture of this congenital disorder.
Keywords: chronic mucocutaneous candidiasis; interleukin-17 receptor A (IL-17RA); staphylococcal infection; family